Analisis Pengendalian Kualitas Produk X dengan Metode Six Sigma di PT. Y - Anggita, Avriella; Satriawan, I Ketut; Wiranatha, Agung Suryawan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): SeptemberDO - 10.24843/JRMA.2021.v09.i03.p07, 2021)
PT. Y is a company that produce various kinds of products which are made from natural ingredient or plants simplicia. One of it is product X which is often found defects on the packaging. The purpose of this research is to analyze the factors that caused defects on the product’s packaging and to propose improvement suggestions by using the six sigma method which consists of Define, Measure, Analyze, Improve and Control (DMAIC) phases. The results of this research showed that the sigma level was 4.11. Through the making of Critical to Quality (CTQ), it has been discovered that there were 3 types of defect, namely a hole found in the plug (0.19%), a crack found in the plug (0.22%), and leaks found in between the plug and the body of the packaging (0.93%). The factors that caused defects on the product’s packaging consisted of human error , material, method and machine. The improvement suggestions that could be recommended are to form an inspection team, to inspect the packaging material from time to time at the supplier’s workplace, to use the checksheet to make it easier when packaging is being inspected, to apply drop test to the packaging which are received from the supplier, and to add a drop test machine so the result of the test would be more accurate. Keywords : six sigma, quality control, bottled oil